Combining corpora with other language resources and tools in pedagogic audiovisual translation - Ivanovska-Naskova, Ruska (Research in Corpus Linguistics, 2023)
This study focuses on the potential of combining various types of language resources and tools in pedagogic audiovisual translation in university level courses. It argues that the direct use of ad-hoc corpora compiled by students can be combined with other tools such as bilingual dictionaries, online resources and subtitling software in performing concrete translation tasks. The study reports on the positive results of the translation activity conducted with students of the degree course in the Italian Language and Literature program at the Ss. Cyril and Methodius University of Skopje in 2018. The first part of the study reflects on certain tendencies in the field of intersection between language pedagogy and audiovisual translation and presents concrete examples of this type of pedagogic tasks applied in teaching Italian as a foreign language. The central part of the study presents various aspects and stages of the activity: its aim, context, choice of video material, the complexity of the language of the videos, the tools used, the translation strategies, the creation of glossary, the revision of the subtitles and the discussion of the feedback. The study concludes with the results of the questionnaire and potential prospects for enhancing the task and reuse of the translated material for compilation of parallel corpus.
Keywords: corpus for pedagogic purposes, audiovisual translation, Italian as a foreign language, Macedonian